Rewarding good taxpayers, an effective mechanism? (2021)
In this paper, I examine the conditions under which rewarding honest taxpayers is an optimal mechanism to reduce tax evasion and improve collection. My theoretical model suggests that when it is expensive to audit contributors, and moral (or pecuniary) evasion cost is high enough, rewarding tax compliance is an effective strategy to increase collection. I provide empirical evidence from Argentina's province variation of rewards policies and tax collection. Where the data suggests that theoretical conditions hold, I find a positive effect in real estate per capita tax collection between 0.4 and more than 2 standard deviations.